Ultrasound-guided interventions for painful shoulder: from anatomy to evidence - Chang, Ke-Vin; Mezian, Kamal; Naňka, Ondřej; Wu, Wei-Ting; Lin, Chih-Peng; Özçakar, Levent (Journal of pain research, 2018)
Shoulder pain is a common musculoskeletal disorder of variable etiology, ranging from rotator cuff pathology to peripheral nerve entrapment. Advances in ultrasound (US) technology have allowed static and dynamic evaluation of shoulder problems and most importantly, offer real-time, radiation-free guidance for interventions. The present review aims to describe shoulder anatomy in detail using information from cadaveric models and to illustrate US-guided techniques using clearly labeled figures and videos. The review will also present evidence of specific US-guided therapies for shoulder pain by summarizing landmark studies, systematic reviews, and meta-analyses. The following shoulder structures will be covered: 1) the biceps long head tendon, 2) the acromioclavicular joint, 3) the subacromial-subdeltoid bursa, 4) the glenohumeral joint, 5) the suprascapular nerve, and 6) the axillary nerve.
Keywords: pain; tendon; rehabilitation; joint; sonography; injection